Educação financeira na perspectiva da educação matemática crítica: uma investigação realizada na zona rural de Ipixuna do Pará/PA - Costa, Hozana Freitas da (2023)
The present dissertation, inserted in the research line Educational practices in Science and Mathematics teaching, presents as its theme Financial Education (FE), by perspective of Critical Mathematics Education (CME) and sought to analyse the potential of FE activities from the perspective of CME, through the development of a guide on the subject for a critical and reflective training of students in the 8th grade of elementary school, in order to answer the guiding question of the research: In what way can activities grounded in Critical Mathematics Education, dealing with Financial Education, contribute to reflection and construction of meanings by 8th grade students? We used as theoretical assumption the CME thought by Professor Ole Skovsmose, specifically in his works from 2000, 2009, 2012, 2013 and 2014 and the PE as presented by Kistemann Jr. (2020, 2021), using as research methodology the Didactic Engineering (DI). Therefore, to validate the research, the proposed activities were applied in a public elementary school located in the rural area of Ipixuna do Pará (PA), with two 8th grade groups. For data collection, the instruments used were teacher-researcher's logbooks and the records of the activities developed by students. The data allowed us to observe that inserting PE themes within a context, thinking in a perspective of education for citizenship, based on dialogue and considering the students' perspectives, can contribute to their engagement, as well as help them develop the ability to reflect about the reality around them and find meaning in classroom practices, building a learning intentionality. The educational product generated by this study was a guide with suggested activities with the following title “Financial Education and Critical Mathematics Education: a teacher's guide”. The guide is organized in three sections, dealing respectively with the topics: Financial Education allied to Environmental Education, Taxes in Everyday Life, and Household Bill Saving. Each section presents a sequence of activities, divided into meetings, seeking to accompany teacher step by step and suggesting materials and adaptations for the insertion of PE themes from a critical perspective. Activities addressed in the product present potential to be worked in scenarios for investigation, constituting a tool for teacher to be inspired and adopted in his classroom practices, through activities that encourage students to expose and build opinions about social issues as part of their daily lives. The educational product that accompanies this dissertation is available at: <http://educapes.capes.gov.br/handle/capes/738156>